Prenatal Maternal Occupational Exposure and Postnatal Child Exposure to Elemental Mercury. Issue 3 (March 2016) - Xu, Jian; Yan, Chong-huai; Hu, Howard; Wu, Mei-qin; Shen, Xiao-ming
Abstract : Objectives: Young children are highly vulnerable to elemental mercury toxicity, and elementary mercury exposure in young children in China unfortunately occurs regularly because of the wide use of fluorescent lamps, glass thermometers, and other mercury-contained items. This study aimed to summarize such recent cases in a referral clinic and to make recommendations for postexposure treatment and prevention of future exposure. Methods: Patients were evaluated between January 2007 and December 2009 in environmental health facilities throughout China and were referred to our clinic. A total of 6 children younger than 4 years with significant elemental mercury exposure were included in this case series analysis. The total mercury content in blood and hair (fetal hair if necessary) and average 24-hour urine mercury concentrations were analyzed. Meso-2, 3-dimercaptosuccinic acid or surgery was prescribed for the patient if necessary. Results: Young children were found to be exposed in 3 ways as follows: prenatal exposure through maternal occupational contact in compact fluorescent-lamp factories (2 cases), broken thermometers (3 cases), and other causes of accidental inhalation of mercury vapor during the embryonic and lactation periods (1 case). For 3 cases caused by broken thermometers, x-ray images helped to identify the position of mercury residues. Local excision was used to remove mercury from the floor of the mouth in 1 case. One child was prescribed oral meso-2, 3-dimercaptosuccinic acid, and a good response was received. Conclusions: Substitution of mercury-in-glass thermometers and vigilance to prevent women of childbearing age from occupational mercury exposure were suggested. Treatment selection should vary according to patient situations.